Aplicación de los estilos de aprendizaje en el bajo rendimiento escolar de los estudiantes del 2do al 7mo año de educación básica de la Escuela de Aplicación Pedagógica del ISPED Los Ríos - parroquia Pimocha - cantón Babahoyo provincia Los Ríos en el periodo lectivo 2010 - 2011 - Rivas Morante, Armando Rigoberto (2011)
The investigation of the styles of learning‟s, in the school yield of the children and girls of the second to the seventh year of basic of the School of Pedagogic Application of the ISPED The Ríos, parish Pimocha - Canton Babahoyo, county the rivers in the Period lectivo 2010-2011. In the face of the necessity of making aware to the educational of this institution that the learning styles influence positively in the school yield don't find experimental data that allow us to detect that the teachers know the styles of their students' learning but rather they work following the contents of the texts without taking into account the evolution of the significant learning and the way of learning how to learn of each one of them. Accepted these limitations, it is summarized basic principles on the styles of learning‟s and the school yield besides some recent proposal about their functionality in the school yield. When analyzing the validity of the interrelation one can show off that the school yield of the children and girls are influenced by the opportunities that are presented to enrich such a process and the learning styles of each one of them that is not more than the way to learn. Almost all the studies of styles of learning‟s are emphasized in the necessity of knowing of what way each since individual only learns by means of this we can look for the best means toward a knowledge that will be used in his daily life, in this investigation after having applied the instruments we could observe with enough approach the lack of opportunities to be able to develop the different learning ways. In what concerns to the school yield and to be related closely to the styles of learning of the human being big holes maybe to the ignorance in the way of learning of the individuals exist, it is that the student in occasions doesn't elevate her yield thanks to the disinformation of the educational one that she doesn't find the form of learning of the student. Grateful the limitations that exist even in the treatment on the learning styles and the school yield, the present work emphasizes basic principles about the styles of learning‟s that demand to know the characteristics of each one of them and its contribution in the school yield. Previous a documentalrevisionabout the factors that diminish the probability of elevating the school yield. It is expected that the effort that we have captured in this work is an enriching contribution to the work of the educational ones and the community educational object of our concern and be the beginning of changes of routine patterns. We have not wanted but looking for strategies that simplify the educational work and that he/she helps us change the mental outline of our students transforming them into competent agents. The task is of all and we also seek to be a reflection of that that exteriorizamos.